2017
DOI: 10.4088/jcp.17m11476
|View full text |Cite
|
Sign up to set email alerts
|

Treatment to Enhance Cognition in Bipolar Disorder (TREC-BD)

Abstract: ClinicalTrials.gov identifier: NCT01470781.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Repetition is the hallmark feature of CCT, and neuroplasticity is its theoretical foundation ( Siegle et al, 2007 ). Cognitive improvements, including EF, have been identified using BrainHQ or similar exercises ( Morimoto et al, 2014 ; Lewandowski et al, 2017 ), and these studies established the empirical basis for the selection of exercises. In addition, exercise selection was based on the provider’s description 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Repetition is the hallmark feature of CCT, and neuroplasticity is its theoretical foundation ( Siegle et al, 2007 ). Cognitive improvements, including EF, have been identified using BrainHQ or similar exercises ( Morimoto et al, 2014 ; Lewandowski et al, 2017 ), and these studies established the empirical basis for the selection of exercises. In addition, exercise selection was based on the provider’s description 1 .…”
Section: Methodsmentioning
confidence: 99%
“…It is worth mentioning that these negative results might be explained by some methodological limitations of the trial, including the length of the intervention (too short) or the fact that patients were subsyndromic at study enrolment. Another study leaded by Lewandowski and colleagues (2017) assessed the efficacy of an internet-based cognitive remediation program in patients with BD compared with an active control group both in neurocognition and community functioning. After treatment, patients who received the internet-based program improved cognitive performance in processing speed, visual learning and memory domains, and the composite score.…”
Section: Restoring Psychosocial Functioning: Therapies That Have Imprmentioning
confidence: 99%
“…Consequently, clinical trials investigating the pro-cognitive effects of candidate cognition treatments have produced overall disappointing or only preliminary results [ 7 , 11 ]. However, evidence from a few small open-label, non-controlled studies suggests that cognitive remediation (CR) may have pro-cognitive effects in patients with BD [ 12 , 13 ], and recent findings from a larger randomized clinical trial of 70 h of computerized CR in remitted patients with BD type I showed improvements on processing speed, visual learning, and memory and a cognitive composite measure [ 14 ].…”
Section: Introductionmentioning
confidence: 99%